Prevention of immune-mediated corneal graft destruction with the anti-lymphocyte monoclonal antibody, CAMPATH-1H. - Newman, D; Isaacs, J; Watson, P; Meyer, P; Hale, G; Waldmann, H (1995)
We report a patient with peripheral rheumatoid corneal melting who developed a corneal perforation in one eye requiring tectonic keratoplasty. Nine consecutive corneal grafts were rapidly destroyed despite systemic immunosuppression with corticosteroid, cyclophosphamide, azathioprine and cyclosporin A. A rejection episode was observed in one graft before it melted and allograft rejection may have contributed to the destruction of other grafts. Corneal graft survival was ultimately achieved by systemic immunosuppression with the anti-lymphocyte monoclonal antibody, CAMPATH-1H. A single episode of rejection developed in the early post-operative period which was easily reversed by topical corticosteroid. Corneal melting has not recurred and the graft has now remained intact and clear for 24 months. Anti-lymphocyte monoclonal antibodies may therefore provide effective immunosuppression in the treatment of refractory ocular disorders.